PENGUATAN KAPASITAS PENDETA DALAM MEMBANGUN PERTUMBUHAN GEREJA YANG SEHAT DAN KONTEKSTUAL DI KABUPATEN SUPIORI - Gernaida Krisna R. Pakpahan; Frans Pantan; Hiruniko Ruben; Anita Rosriyanti Sofia Ratu; Rafles Ngilamele (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2026)
This community service program aimed to strengthen pastors’ capacity in developing healthy and contextual church growth in Supiori Regency. The program was grounded in the strategic role of the church within Supiori’s socio-religious structure, as indicated by the presence of 71 Protestant churches and 1 Catholic church out of 73 recorded houses of worship. This condition demonstrates that the church functions not only as a place of worship but also as a key institution for faith formation, value education, community strengthening, and socio-spiritual development. However, the significant number of churches does not automatically indicate healthy church growth, particularly in relation to discipleship, leadership regeneration, congregational empowerment, pastoral leadership, and the relevance of ministry to local needs. The program employed educational, participatory, and contextual approaches through material presentation, focused discussion, ministry reflection, experiential dialogue, and the identification of practical church-related issues. The results show that the activity strengthened pastors’ understanding of church growth as a multidimensional process involving spiritual health, leadership, organization, ministry effectiveness, discipleship, and social impact. The program also encouraged pastors to critically reflect on ministry practices that remain overly dependent on pastoral figures and to move toward more participatory, collaborative, and sustainable ministry models. Therefore, this community service activity contributes to strengthening local church leadership as part of the socio-spiritual development of Supiori society. ABSTRAKKegiatan Pengabdian kepada Masyarakat ini bertujuan untuk memperkuat kapasitas pendeta dalam membangun pertumbuhan gereja yang sehat dan kontekstual di Kabupaten Supiori. Latar kegiatan ini berangkat dari kuatnya posisi gereja dalam struktur sosial-keagamaan masyarakat Supiori, yang ditandai dengan keberadaan 71 gereja Protestan dan 1 gereja Katolik dari 73 rumah ibadah yang tercatat. Jumlah tersebut menunjukkan bahwa gereja memiliki peran strategis dalam pembinaan iman, pendidikan nilai, penguatan komunitas, dan pembangunan sosial-spiritual masyarakat. Namun, besarnya jumlah gereja belum selalu sejalan dengan kualitas pertumbuhan gereja, terutama dalam aspek pemuridan, kaderisasi pelayan, pemberdayaan jemaat, kepemimpinan pastoral, dan relevansi pelayanan terhadap kebutuhan lokal. Metode pelaksanaan kegiatan menggunakan pendekatan edukatif, partisipatif, dan kontekstual melalui penyampaian materi, diskusi terarah, refleksi pelayanan, dialog pengalaman, serta identifikasi persoalan gerejawi di lapangan. Hasil kegiatan menunjukkan adanya penguatan wawasan para pendeta mengenai pertumbuhan gereja sebagai proses multidimensional yang mencakup kesehatan spiritual, kepemimpinan, organisasi, pelayanan, pemuridan, dan dampak sosial. Kegiatan ini juga mendorong para pendeta untuk merefleksikan ulang praktik pelayanan yang terlalu bergantung pada figur pendeta menuju model pelayanan yang lebih partisipatif, kolaboratif, dan berkelanjutan. Dengan demikian, PKM ini berkontribusi dalam memperkuat kepemimpinan gerejawi lokal sebagai bagian dari pembangunan sosial-spiritual masyarakat Supiori.